MAKNA DEMOKRASI DALAM ISLAM - Sirajuddin Fikri (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
Discourse on the relationship between Islam and democracy has never been brought into intellectual debates in this country. Discussions on this issue emerge is Dcradically and incompletely, so that it tends to bewilder and stimulate simplification aStude among Muslims. Till now, most discourses give more concerns about pro-contra on the implementation or formulation of Islamic law. This article attempts to discuss atemocracy issue in its proportional portion according to Islamic perspective. Kata kunci: - the Islamic democracy, -the West demokrasi Barat, -comparison